If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -7(3x + 3) = -126 Reorder the terms: 6x + -7(3 + 3x) = -126 6x + (3 * -7 + 3x * -7) = -126 6x + (-21 + -21x) = -126 Reorder the terms: -21 + 6x + -21x = -126 Combine like terms: 6x + -21x = -15x -21 + -15x = -126 Solving -21 + -15x = -126 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -15x = -126 + 21 Combine like terms: -21 + 21 = 0 0 + -15x = -126 + 21 -15x = -126 + 21 Combine like terms: -126 + 21 = -105 -15x = -105 Divide each side by '-15'. x = 7 Simplifying x = 7
| 5(5-x)(5+x)=55 | | -2/7x12/25 | | 2r^4=7r^2-2 | | 10/x=12/5 | | -2/7x_12/25 | | 10/x=5/12 | | x^2-9+1-3x=x^2-4+4x-5 | | 6x^2+16x+10=0 | | (1.7)1/5 | | 6abc=18ac | | 30-5=15x-35 | | 10x+20-10=3x | | 12x+4=4x+8 | | x/9=10/5 | | 0.04(x+200)=900x | | 0.04(x+200)=900+200x | | 1/2(v-3)=2v*3/2 | | 3r+10r+8= | | 3x+15b=17 | | 1/2(2-3)=2v*3 | | x^2+20x+31=6x-2 | | 0=5x^2+25x | | 28y+6=3 | | 7/x=8/3 | | 15x^2-35x-6=0 | | 3x+6y=8x-2 | | 72k-18=0 | | 3x-6y=8x+y | | 12.4+1.5x= | | 18x-(2x-9)=7 | | (3x+2)(-5-4)=0 | | 3x+6y=8-2 |